The Penile Microbiota in Uncircumcised and Circumcised Men: Relationships With HIV and Human Papillomavirus Infections and Cervicovaginal Microbiota - Onywera, Harris; Williamson, Anna-Lise; Ponomarenko, Julia; Meiring, Tracy L. (Frontiers in Medicine, 2020)
While the human microbiota especially that of the gut, cervix and vagina continue to receive great attention, very little is currently known about the penile (glans, coronal sulcus, foreskin, and shaft) microbiota. The best evidences to date for the potential role of the penile microbiota in human immunodeficiency virus (HIV) and other sexually transmitted infections (STIs) acquisition have come from studies examining medical male circumcision. We are still at the foothills of identifying specific penile bacteria that could be associated with increased risk of STI/HIV acquisition. In this review, we summarize the available literature on the human penile microbiota and how it is impacted by circumcision. We also discuss the potential role of penile microbiota in STIs and its impact on cervicovaginal microbiota. Taken together, the findings from the penile microbiota studies coupled with observational studies on the effect of male circumcision for reduction of STI/HIV infection risk suggest that specific penile anaerobic bacteria such as Prevotella spp. potentially have a mechanistic role that increases the risk of genital infections and syndromes, including bacterial vaginosis in sexual partners. Although penile Corynebacterium and Staphylococcus have been associated with healthy cervicovaginal microbiota and have been found to increase following male circumcision, further investigations are warranted to ascertain the exact roles of these bacteria in the reproductive health of men and women. This review aims to address existing gaps and challenges and future prospects in the penile microbiota research. The information described here may have translational significance, thereby improving reproductive health and management of STI/HIV.